2014
DOI: 10.3389/fnins.2014.00150
|View full text |Cite
|
Sign up to set email alerts
|

The speed-accuracy tradeoff: history, physiology, methodology, and behavior

Abstract: There are few behavioral effects as ubiquitous as the speed-accuracy tradeoff (SAT). From insects to rodents to primates, the tendency for decision speed to covary with decision accuracy seems an inescapable property of choice behavior. Recently, the SAT has received renewed interest, as neuroscience approaches begin to uncover its neural underpinnings and computational models are compelled to incorporate it as a necessary benchmark. The present work provides a comprehensive overview of SAT. First, I trace its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

43
641
9
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 685 publications
(698 citation statements)
references
References 205 publications
(315 reference statements)
43
641
9
5
Order By: Relevance
“…This is an 272 expected range of reaction times in psychophysical choice tasks. It is consistent with 273 oscillatory changes in the BG [34] and sensorimotor cortex [35] during animal decision 274 making tasks, as well as choice reaction times in mental chronometry studies in 275 humans [36][37][38]. However, the equation (6) after the first 500 ms. An exception to this rule was the case of alpha oscillations, where 300 effectiveness had a second sharp rebound spike, with a surprisingly similar duration and 301 onset among runs.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…This is an 272 expected range of reaction times in psychophysical choice tasks. It is consistent with 273 oscillatory changes in the BG [34] and sensorimotor cortex [35] during animal decision 274 making tasks, as well as choice reaction times in mental chronometry studies in 275 humans [36][37][38]. However, the equation (6) after the first 500 ms. An exception to this rule was the case of alpha oscillations, where 300 effectiveness had a second sharp rebound spike, with a surprisingly similar duration and 301 onset among runs.…”
supporting
confidence: 58%
“…Evidence suggests that oscillations in some 34 certain bands in the striatum and the subthalamic nucleus (STN), the input structures 35 of the BG, are driven by cortical regions [22][23][24][25]. Taking this into account, in previous 36 work [26] we explored the impact of cortical rhythmic activity on the BG function and 37 we found that the former can completely shape which areas of the BG circuit are active. 38 Yet, the connection between the BG, cortical oscillations and decision making still 39 remains relatively unexplored.…”
mentioning
confidence: 96%
“…Deliberate, top-down SATs have been the subject of extensive investigation in psychology, traditionally studied by manipulating either the subject's goals (e.g. respond fast vs. respond accurately) or by controlling the subjects RT directly via response cues (Heitz 2014). However, such voluntary criterion modulations are relatively slow, effortful, and require executive control based on intricate understanding of the context, making them inefficient for dealing with trial by trial variations in decision values.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that BSI can serve as a top-down control mechanism to rapidly and parametrically trade between speed and accuracy, and such a cognitive control signal presents both when the subjects emphasize accuracy or speed in perceptual decisions. decision making; speed-accuracy tradeoff; top-down control; balanced input THE ABILITY TO DYNAMICALLY adjust speed vs. accuracy is a salient feature of decision-making (Bogacz et al 2010; Gold and Shadlen 2002;Heitz 2014;Wang 2008;Wickelgren 1977): if "to get it right" is the priority, we slow down to gather more information and gain a better performance. On the other hand, if time is at a premium (e.g., when detecting a predator), we make a quick judgment at the potential cost of accuracy.…”
mentioning
confidence: 99%